Project Management in the Implementation of Long-term Interregional Initiatives - A. V. Kotov (Управленческое консультирование)
The article develops to the analysis of the application of project management in the implementation of long-term interregional initiatives. The relevance of the study is due to modern experience in initiating and implementing major interregional initiatives. Practice shows that they need no alternative real project content, i. e. the availability of interconnected local investment projects, the implementation of each of which together provides high interregional (macro-regional) and region-wide importance. To date, there is a shortage of projects at the interregional level in Russia. This problem is recorded in the national Spatial Development Strategy.We formulate an author’s approach to defining of the interregional initiative as an activity to develop, present and launch a significant large complex interregional project (a set of interconnected investment and other related projects), potentially capable of having a significant impact on the social and economic development of the country, the federal district / macro-region.The study analysed detail the lessons learned from project management at the regional level, which can be useful for the implementation of integrated interregional initiatives. The main models of “spillovers” of experience of implementation of project management from federal to regional level for development of own initiatives of subjects of the Russian Federation (direct transfer, reset of state programs, project management of new spatial forms of organization of economic activity, initiation of joint projects with federal development institutions, etc.) are given.We have underlined possibilities project management in promoting interregional initiatives should focus on the following areas: taking into account innovative opportunities concentrated in systemically important economic complexes; Ranking projects in terms of effects for regional business communities. Projects involving and combining local resources should benefit.In regard with innovation development, we have proposed specific attention to interregional initiatives related to the acquisition of new knowledge, associations of the potential of regional scientific centers, synthesis of accumulated knowledge in the form of patents, advanced technologies, industrial models.